انعكاسات إلغاء الامتحان النهائي لمادة التربية البدنية والرياضية على عمل الأستاذ أثناء الحصة - تواتي، حياة; الحاج، بن خالد; عطا الله، أحمد (جامعة محمد بوضياف المسيلة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2020)
هدفت الدراسة إلى التعرف على انعكاسات إلغاء الامتحان النهائي لمادة التربية البدنية والرياضية على عمل الأستاذ والتلميذ وذلك من وجهة نظر أساتذة التربية البدنية والرياضة المشرفين على الأقسام النهائية. ولهذا الغرض افترضنا بأن إلغاء الامتحان النهائي لمادة التربية البدنية والرياضية كان له انعكاس إيجابي على عمل الأستاذ وأداء التلميذ في حصة التربية البدنية والرياضية. ومن أجل تحقق من هذا الفرض استخدمنا المنهج الوصفي بطريقة المسح، حيث قمنا بإعداد استبيان وقدم إلى أساتذة مادة التربية البدنية والرياضية المشرفين على الأقسام النهائية وقدر عددهم (155) أستاذ. بعد جمع النتائج وتفريغها ومعالجتها معالجتها إحصائيا. توصلت الدراسة إلى أن إلغاء الامتحان له انعكاس إيجابيا على عمل الأستاذ من حيث تدابير التقويم وساعده في فرض المزيد من الانضباط في حصة التربية البدنية والرياضية، أما بالنسبة للتلميذ فهذا الإلغاء فرض عليه المزيد من الانضباط والصرامة في الأداء أثناء حصة التربية البدنية والرياضية. وعليه أوصينا بضرورة توحيد سلم التنقيط على مستوى الوطن لجميع الأنشطة الفردية والجماعية، وأن يتميز أستاذ المادة بشخصية قوية ومؤثرة على التلاميذ بالإيجاب حتى يحبون المادة أكثر ويهتمون بها.
The objective of this research is to know the extent to which the cancellation of sports education final examination influences on the work of teachers responsible for the final classes and pupils of such classes. Thus, we adopted a main question: will the cancellation of the final examination of physical education and sports influence the work of the teacher and the learner in physical and athletic education sessions? We assumed that the cancellation of the final exam would have some influence on the work of the teacher and the learner in the physical education sessions. To test this hypothesis, we use a descriptive method using a questionnaire sent to 155 teachers in charge of final classes (pupils in 3rd A.S, the 4th year AM). After retrieving the answered questionnaires, we treated the responses using a variety of statistical. The analysis of the data from the questionnaires confirmed that the cancellation of the final examination of physical education and sports did indeed influence the work of the teachers, who invented new evaluation strategies, to impose more disciplines in working sessions. As for the students, they were obliged to prove more discipline and attendance in physical education and sports sessions. In conclusion, we can present some proposals, including the need to unify the assessment scale at the national level for all individual and collective activities and the need for the teacher to have a strong influential personality to master the classes and to give pupils good example and encourage them to become more interested in the subject.
Keywords: التعليم الجامعي -- طلبة الجامعات -- التربية البدنية -- التربية الرياضية -- أساتذة التربية الرياضية -- الجزائر